A Case Study on Entrepreneurial Motivation and Challenges faced by Women in Agri-entrepreneurship in Nepal - Nepal, Dipesh; Poudel, Srijana (Journal of Forest and Livelihood, 2024)
Women empowerment, community development, and poverty reduction can be achieved by promoting agri-entrepreneurship in Nepal. In recent years, women have started to enter agrientrepreneurship, generating employment opportunities and raising the economic conditions of their families. However, they face various difficulties due to social and cultural structures. This study aims to assess the current situation of women in agri-entrepreneurship, identify the major motivational factors for women to initiate start-ups, explore the challenges faced by female agrientrepreneurs, and identify favorable policies for promoting women’s agri-entrepreneurship. A case study design and secondary review was used, and data were collected through in-depth interviews with women agri-entrepreneurs. The statistical data showed that only 8.22 per cent of agriculture, fishing, and forestry establishments are owned by females and only 14.8 per cent have female managers. Financial freedom, self-fulfillment, and employment generation were the major motivational factors for initiating startups. Similarly, the major challenges faced by women agri-entrepreneurs were limited land ownership, inadequate access to financial services, male family members’ dominance, and doubt about women’s capability. So, this study suggests that providing financial assistance, organizing training and vocational courses, and providing extension and advisory services will promote women’s agri-entrepreneurship in Nepal.